A generic wake analysis tool and its application to the Japan Bulk Carrier test case. (1st January 2019) - Maasch, Matthias; Mizzi, Kurt; Atlar, Mehmet; Fitzsimmons, Patrick; Turan, Osman
Abstract: Economic pressures and regulatory obligations have brought about a great interest in improving ship propulsion efficiency. This has motivated and directed research to improve the hydrodynamic performance of a vessel thus seeking the development and generation of optimised designs. When analysing flow characteristics of a vessel, particular attention is given to analysing its wake field and stern flow characteristics. For the detailed analysis of the wake flow field, a Wake Analysis Tool (WAT) was developed within the programming environment of a commercial CAE tool. The WAT is based on a framework that enables easy interaction to an external CFD solver reading flow field properties from a generic csv file. The wake flow field is visualised and analysed in schematic form according to the standard and customized (i.e. the British Ship Research Association criteria) wake analyses. By coupling the CAE tool with a commercial flow solver, an example was given how to use the wake tool in a fully automated simulation process. Finally, the wake tool was used to analyse the nominal propeller wake flow of the Japan Bulk Carrier (JBC) thus showing how it can be efficiently applied to a set of numerical results. Graphical abstract: Highlights: Introduction of the functionality of a custom-developed propeller Wake Analysis Tool. Tool extension that includes the B.S.R.A. criteria assessment. Tool integration into a software chain to perform an automated design study. Automated analysis of Japan Bulk Carrier wake field at different speeds and drafts. Numerical Results Verification and Validation for JBC baseline conditions.